The Theory of Planned Behavior and the Earned Income Tax Credit - Lloyd Zimmerman; Anthony Canale; Sonya L. Britt; Martin Seay (Journal of Financial Therapy, 2015)
The Earned Income Tax Credit (EITC) seeks to reduce poverty and provide the resources necessary for an individual to become self-sufficient. The EITC achieves this annually by lifting millions of households above the poverty level through income supplementation. However, recent evidence suggests that the long-term upward economic mobility provided by the EITC in practice is limited. To investigate the factors associated with achieving this financial independence, this study utilized the Theory of Planned Behavior to determine if (a) attitudes—as measured by time preference and self-esteem, (b) subjective norms—as measured by education, parents’ poverty level or work status, and religiosity, and/or (c) perceived behavioral control—as measured by self-efficacy (perceived effectiveness in accomplishing tasks) were significant in moving beyond qualification standards of the EITC. Using data from the National Longitudinal Survey of Youth (NLSY79), the EITC utilization pattern of a sample of 178 individuals was investigated. Results reaffirmed the economic advantages of marriage, suggesting that, by protecting and support healthy marriages, financial therapists can actively contribute to improved financial outcomes. Results also indicated that individuals with a high degree of mastery (feeling in control) were more likely to experience economic improvement, as measured through movement above EITC qualification standards. This suggests that financial therapists should work to facilitate growth in personal mastery as a part of helping clients reach their financial goals.
Keywords: Earned Income Tax Credit (EITC); Theory of Planned Behavior; self-esteem; efficacy; financial therapy